2011
DOI: 10.1111/j.1540-8159.2011.03054.x
|View full text |Cite
|
Sign up to set email alerts
|

Complete Atrioventricular Block As the First Manifestation of Noncompaction of the Ventricular Myocardium

Abstract: Noncompaction of ventricular myocardium (NVM) is a rare cardiomyopathy, most probably caused by disturbances in embryonic morphogenesis of the myocytes, resulting in prominent trabeculations in the ventricular myocardium. Several diagnostic criteria have been proposed by echocardiography, and its association with other heart diseases is common. Its mortality is closely related to ventricular dysfunction, cardiac arrhythmias, and cardioembolic events. We report here a case of occurrence of atrioventricular bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…1e5 Among these cases, only two cases were associated with biventricular Table 1 Clinical features and management profile of all previously reported cases of NCVM with CHB. Variables noncompaction, 1,4 whereas, other cases were associated with isolated left ventricular noncompaction 2,3,5 (Table 1). Our case had biventricular NCVM with dilated cardiomyopathy, concomitant valvular insufficiency and complicated with complete AVB.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…1e5 Among these cases, only two cases were associated with biventricular Table 1 Clinical features and management profile of all previously reported cases of NCVM with CHB. Variables noncompaction, 1,4 whereas, other cases were associated with isolated left ventricular noncompaction 2,3,5 (Table 1). Our case had biventricular NCVM with dilated cardiomyopathy, concomitant valvular insufficiency and complicated with complete AVB.…”
Section: Discussionmentioning
confidence: 98%
“…NCVM is increasingly recognized as an important cause of cardiomyopathy and it is the result of the arrest of cardiac lesion densification process and characterized by excessively prominent trabeculations in ventricular wall segments and deep intratrabecular recesses. 4 It is diagnosed primarily by echocardiography. 5 The most frequently applied echocardiographic definition of NCVM was established by Jenni et al, defined NVMC as the ratio of the end-systolic thickness of noncompacted/ compacted myocardium of greater than 2.0.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of function of hNav 1.5 by a ZASP1 mutation is associated with interventricular conduction disturbance in LVNC [10]. Several cases of LVNC and conduction abnormalities were reported [1,8,9,[11][12][13][14][15]. Familial occurrence has been reported by Taniguchi et al where LVNC and conduction block were found in two siblings of the indexed patient [12].…”
Section: Genetics and Conduction Abnormalitiesmentioning
confidence: 80%
“…Her TTE confirmed LVNC by the presence of numerous and prominent trabeculations. 14 Jackson et al similarly described the case of a patient diagnosed with non-compaction after the occurrence of complete atrioventricular block with syncope. After noncompaction was diagnosed on TTE, this patient had a dual-chamber ICD implanted, and went on to develop ventricular tachycardia.…”
Section: Bradyarrhythmiasmentioning
confidence: 99%